2018
DOI: 10.1001/jamainternmed.2017.8628
|View full text |Cite
|
Sign up to set email alerts
|

Unrecognized Cardiovascular Emergencies Among Medicare Patients

Abstract: described diagnostic error as the next frontier in patient safety and highlighted a critical need for better measurement tools.OBJECTIVES To estimate the proportions of emergency department (ED) visits attributable to symptoms of imminent ruptured abdominal aortic aneurysm (AAA), acute myocardial infarction (AMI), stroke, aortic dissection, and subarachnoid hemorrhage (SAH) that end in discharge without diagnosis; to evaluate longitudinal trends; and to identify patient characteristics independently associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 18 publications
1
27
0
1
Order By: Relevance
“…5 In the emergency department (ED), the likelihood varies widely by diagnosis and ranges from 0.6% to 35%. [6][7][8][9][10][11][12] Many diagnostic errors are associated with the potential for moderate to severe harm. 13 Previous studies on closed ED malpractice claims have demonstrated that most errors are the result of a failure to make a diagnosis.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…5 In the emergency department (ED), the likelihood varies widely by diagnosis and ranges from 0.6% to 35%. [6][7][8][9][10][11][12] Many diagnostic errors are associated with the potential for moderate to severe harm. 13 Previous studies on closed ED malpractice claims have demonstrated that most errors are the result of a failure to make a diagnosis.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…Diagnostic delays are increasingly being recognized as an important threat to patient safety [ 21 ]. To date, little is known about the incidence of and risk factors for diagnostic delays, and most prior work has focused on myocardial infarction and stroke [ 19 ]. Beyond diseases affecting the cardiovascular system, diagnostic delays associated with infectious diseases may be especially important to consider, given that delays in the treatment of infectious diseases are associated with worse clinical outcomes [ 22–27 ], herpes simplex encephalitis is one such disease.…”
Section: Discussionmentioning
confidence: 99%
“…To estimate the frequency and duration of missed opportunities, we used an approach similar to Waxman et al [ 19 ], which has also been used to identify diagnostic delays associated with tuberculosis [ 20 ]. This approach begins by using a case-crossover-type approach to estimate the likely number of missed opportunities based on SSD-associated visits.…”
Section: Methodsmentioning
confidence: 99%
“…Sampling, eligibility, recruitment, informed consent and data collection Part 1: individual patient case as the unit of observation Sampling We will use purposive sampling of patients presenting to the ED who are at higher risk for diagnostic mishaps such as those with undifferentiated symptoms of abdominal pain, fever, chest pain or shortness of breath. [22][23][24][25][26][27] While data has linked chest pain symptoms with a wide range of never-miss conditions, 23 27 limited research has explored shortness of breath and never-miss conditions. Both symptoms will be included as they represent undifferentiated symptoms commonly seen in the ED that have been associated with missed diagnosis.…”
Section: Settingmentioning
confidence: 99%